Blenda ternária de PEAD e PP com PS via compatibilização reativa por Friedel-Crafts - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2015)
The reactive compatibilization of Friedel-Crafts has been applied in binary blends of polyolefins and polystyrene aiming reuse of post consumer polymers. The chemical route is solely applied at pairs polymeric. In this work, the Friedel-Crafts alkylation reaction, catalyzed with aluminum chloride, was employed by the first time as chemical route in the in situ compatibilization for a ternary blend of high density polyethylene (HDPE) and polypropylene (PP) with polystyrene (PS). Two compositions – 50/30/20 and 40/40/20 – with pure homopolymers were studied in echo to fraction of local plastics post-consumer. The graft of alkyl groups in benzene ring of PS was accessed by a combination of Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR). At first, the reactive compatibilization was indirectly determined through the absorbance indices in the linkages of aromatic ring. In the second group of spectrums the benzene ring psubstitution is directly detected and quantified. The changes caused in morphological structure were observed by electronic microscopic (FEG) together with the analyses on particle size (ImageJ software). The thermal characterization via differential scanning calorimetry (DSC) and gravimetric analysis (TGA), more the mechanic properties extracted by tensile test corroborate the effects of a compatibilized agent in comparison to physical blends. The Soxhlet extraction allowed quantify a mass ratio on the compatibilized agent formed. After the phase of PS had extracted by solvent of physical and reactive blends, the absorbance indices detected the presence of the aromatic ring in the reactive samples more than in the physical ones. NMR spectrums identified the signs of the p-substitution plus the signs of specimens arising from of reactive compatibilization. With the increase on the concentration of catalyst the amount of compatibilizer increased followed by a larger degradation in the chains of PS and PP. The morphology imposed by the reactive synthesis shifts the PS domains on the PP phase to HDPE phases, implying preference of HDPE-g-PS copolymer in relationship at the PP-g-PS. Nevertheless, the FTIR and DSC of the residual of soxhlet extraction revealed that the compatibilizer had in your chemical structure more PP segments than HDPE, what could not be proved by the NMR. There was an 80% of reduction in PS domain after the reactive compatibilization in 0,3 % at mass of catalyst amount. The DSC showed migration of PEAD and PP polymer chains to the copolymerized agents. Improves in the thermal parameters indicated a delay at sliding of the interfaces caused through anchoring effects of the compatibilizer. The mechanical variables proved the relationship between the amount of catalyst and the emulsion curve obtained by quantitative analyses on ImageJ software. With 0,3% of catalyst there was improves for elongation at break, tensile strength, toughness and elastic modulus. The investigation proved the availability of the Friedel-Crafts reaction in compatibilization of ternary blends, having the NMR as the best technique to characterization of the material.
Keywords: Blenda ternária; Compatibilização; Friedel-Crafts; Interface; Morfologia; Compatibility; Friedel-Crafts; Interface; Morphology; Ternary blend; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA